Successful use of splenectomy in a patient with hepatitis C virus-related thrombocytopenia - Xilian Huang; Yaping Xie; Daquan Gao; Pengfei Shi; Shenxian Qian (Journal of Infection in Developing Countries)
This case report describes a 44-year-old female with hepatitis C virus-related thrombocytopenia. The laboratory tests showed a platelet count of 3×109/l, positive HCV serology and high serum concentration of HCV-RNA of 6.74×106 copy/ml. She was refractory to standard therapies including corticosteroids, intravenous immunoglobulin (IVIG), thrombopoietin (TPO) and even interferon (IFN) regimens, due to the persistence of a low platelet count. At first, splenectomy was thought to be impossible, but then splenectomy was successfully performed and patient showed good tolerance and a constant normal platelet count after surgery. In conclusion, splenectomy is feasible in selected patients and may allow us to acquire a reasonable platelet count and completion of an anti-HCV protocol. Low platelet count itself should not be the contraindication of operation specifically for these patients. Further studies in larger numbers of patients and over a longer period of time are warranted.